Perbandingan Lama Adaptasi Lensa Bifokal Dan Progressive Addition Lens (PALs) Terhadap Kenyamanan Pasien Di Optik Kota Padang - ., Ermi Yusfita (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This paper discusses the comparison of the length of adaptation bifocal lenses and Progressive Addition Lenses (PALs) to patient comfort in optics Pariaman City. This study aims to reveal: (1) The effect of the use bifocal lenses and PALs on patient comfort in the optics Pariaman City, (2) The process of adaptating bifocal lenses and PALs to the comfort of activities patients in optics Pariaman City. The type of research used is a quantitative descriptive approach. The population in this study were presbyopia patients who used bifocal lens glasses and PALs. Sampling using the Slovin formula. Data were collected through questionnaires and research instruments using a check list. The results of the research of respondents in the optics Pariaman City were 53 respondents including 18 respondents who wore bifocal lenses and 35 respondents who wore PALs. Respondents who felt the effect of using bifocal lenses and PALs in the optics of Kota Pariaman were 0 respondents (0%) and those who did not feel the effect of using bifocal lenses were 18 respondents (100%) and PALs were 35 respondents (100%). While the respondents who felt the process of adapting the use of bifocal lenses in the optics Pariaman City were 18 respondents (100%) and PALs were 35 respondents (100%) and 0 respondents (0%) did not feel the process of adaptation to the use of bifocal lenses and PALs. Based on the results of this study, there are several suggestions, namely: (1) It is recommended for researchers and RO to learn more material about lenses and lens adaptation process, (2) It is hoped the academy will add books reference sources about lenses and lens adaptation processes, (3) It is hoped that the public will ask the RO for education about lenses and lens adaptation before buying glasses.